Artificial intelligence and intellectual property - LEE, Jyh-An (Institutional Knowledge at Singapore Management University, 2021)
This is a book on AI and law. Beginning with a concise but clear explanation of the programming techniques behind AI systems, the book provides a comprehensive account of the intersection between this new software technology and the intellectual property system. From the many ways AI improves the mechanics of IP-related government administration, to legal handling of the copying of data required for much AI to work, to profound questions such as human-assisted creativity and machine generation of IP-covered works, the editors and contributors cover all the crucial issues.